2020
DOI: 10.1093/eurheartj/ehaa845
|View full text |Cite
|
Sign up to set email alerts
|

Clonal haematopoiesis in chronic ischaemic heart failure: prognostic role of clone size for DNMT3A- and TET2-driver gene mutations

Abstract: Aims Somatic mutations of the epigenetic regulators DNMT3A and TET2 causing clonal expansion of haematopoietic cells (clonal haematopoiesis; CH) were shown to be associated with poor prognosis in chronic ischaemic heart failure (CHF). The aim of our analysis was to define a threshold of variant allele frequency (VAF) for the prognostic significance of CH in CHF. Methods and results We analysed bone marrow and peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
70
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(92 citation statements)
references
References 23 publications
7
70
3
2
Order By: Relevance
“…This indicates that the presence of small clones is also linked to ageing and possibly age-related phenotypes, and that with time small clones may become large enough to become clinically relevant. The importance of small clones is supported by a recent study in which VAFs significantly lower than the CHIP level for DNMT3A and TET2 mutations were associated with impaired survival in patients with chronic ischemic heart failure 17 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This indicates that the presence of small clones is also linked to ageing and possibly age-related phenotypes, and that with time small clones may become large enough to become clinically relevant. The importance of small clones is supported by a recent study in which VAFs significantly lower than the CHIP level for DNMT3A and TET2 mutations were associated with impaired survival in patients with chronic ischemic heart failure 17 .…”
Section: Discussionmentioning
confidence: 92%
“…The 2% VAF cut-off for CHIP clones is arbitrary and was chosen largely because of earlier technical limitations. However, a recent study identified a lower VAF threshold that is associated with worse outcome in patients with heart failure 17 . Unresolved questions include additional health consequences of smaller clones and how they evolve over time.…”
Section: Introductionmentioning
confidence: 96%
“…CHIP with a VAF of as little as 10% was sufficiently associated with ASCVD risk [ 65 ]. More remarkably, CHIP due to mutations in DNMT3A or TET2 with a VAF 2% or less was associated with incident heart failure and also worse prognosis with heart failure in a dose dependent manner [ 49 , 50 , 66 ]. A potential explanation for how a minor population of immune cells carrying a DNMT3A or TET2 mutation may influence the local environment (e.g., atherosclerotic plaque) through expansion and/or remodeling noncell autonomously through secretion of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 The most commonly mutated genes in CHIP are the DNA methyltransferase DNMT3A and the DNA demethylase TET2, both of which were experimentally shown to regulate the inflammatory response of circulating leukocytes, increase release of inflammatory cytokines (including IL-1β, IL-6, TNF-α and INF-γ) and accelerate atherosclerosis and heart failure (HF) development in mice. 5 , 6 , 7 , 8 , 9 , 10 , 11 Recent studies 12 , 13 , 14 , 15 using targeted sequencing showed that DNMT3A- and TET2-CH-driver mutations were associated with profoundly impaired long-term survival and increased disease progression in patients with chronic HF, or aortic valve stenosis undergoing transfemoral aortic valve implantation. Despite use of various therapies, recurrent ischemic events or HF continue to occur in some patients post-myocardial infarction (MI), which are considered to be associated with chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%